Insuring Growth : The Impact of Disaster Funds on Economic Reconstruction in Mexico - de Janvry, Alain; del Valle, Alejandro; Sadoulet, Elisabeth (World Bank, Washington, DC, 2016)
Climate change has considerably increased the likelihood of experiencing extreme weather events. Governments in developing countries have a limited capacity to smooth the losses created by extreme weather, and could potentially benefit from the introduction of disaster funds, that is, ex-ante budgeting allocations for post-disaster reconstruction. So far the implementation of disaster funds has been limited, in part because it is still unclear whether disaster funds provide a cost-effective way of coping with these losses. By taking advantage of the sharp rules that govern the municipal-level eligibility for reconstruction funds in Mexico, this paper provides some of the first estimates of the impact of disaster funds on local economic activity. The main finding is that access to disaster funding boosts local economic activity between 2 and 4 percent in the year following the disaster. Another finding is that the positive impact of disaster funds on local economic recovery can persist for as long as a year and a half after the disaster. Consistent with these findings, we additionally show that access to disaster funding leads to a large and sustained 76 percent increase in the growth of local construction employment. This labor market impact slightly precedes the overall increase in local economic activity.